2021
DOI: 10.7717/peerj.12584
|View full text |Cite
|
Sign up to set email alerts
|

Functional macrophyte trait variation as a response to the source of inorganic carbon acquisition

Abstract: Background This study aims to compare variation in a range of aquatic macrophyte species leaf traits into three carbon acquisition groups: HCO3−, free CO2 and atmospheric CO2. Methods The leaf functional traits were measured for 30 species from 30 softwater lakes. Macrophyte species were classified into (1) free CO2, (2) atmospheric CO2 and (3) bicarbonate HCO3− groups. In each lake we collected water samples and measured eight environmental variables: depth, Secchi depth, photosynthetically active radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The δ 13 CORG and δ 15 NORG values of aquatic vegetation, especially submerged macrophytes, are characterized by very high variability dependent on the environmental conditions in which they thrive [5,[13][14][15][16]43]. However, for certain species, habitat differences are not always clearly reflected in their isotopic values [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The δ 13 CORG and δ 15 NORG values of aquatic vegetation, especially submerged macrophytes, are characterized by very high variability dependent on the environmental conditions in which they thrive [5,[13][14][15][16]43]. However, for certain species, habitat differences are not always clearly reflected in their isotopic values [14].…”
Section: Discussionmentioning
confidence: 99%
“…and Sm. produces different types of leaves in fast-flowing rivers, shallow eutrophic lakes, or shallow, softwater lakes [5]. Similarly, Myriophyllum alterniflorum DC., found in a relatively wide range of lake fertility conditions, displays high plasticity in morphological features, as demonstrated by its growth on various substrates [6].…”
Section: Introductionmentioning
confidence: 99%
“…Two decades ago, functional approaches emerged that allowed us to rebuild community ecology and establish general principles regarding assembly mechanisms (Calow, 1987; McGill et al., 2006). Since then, studies based on functional traits (morphological, physiological, and phenological characteristics that directly or indirectly impact individual performance through growth, reproduction, or survival) have been conducted in terrestrial (e.g., Garnier et al., 2001; Violle et al., 2007; Albert et al., 2010a), and aquatic plant communities (Yang et al., 2004; Fu et al., 2013, 2014; Luo et al., 2016; Su et al., 2019; Zhang et al., 2019; Chmara et al., 2021; Ma et al., 2022a, 2022b). Functional approaches have revealed that marked trait variation occurs in the field at inter‐ and intraspecific levels in response to a range of biological processes operating at different spatial and temporal scales, ultimately leading to species coexistence (Messier et al., 2010; Albert et al., 2010a; Taudiere & Violle, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of charophytes is vital for nutrient cycling in lake ecosystems (Kufel and Kufel 2002; Vermaat et al 2020; Sand‐Jensen et al 2021). Another feature of charophytes is their ability to use bicarbonates as a source of carbon for photosynthesis (Van den Berg et al 2002; Sand‐Jensen et al 2018, 2021; Chmara et al 2021). This property may give charophytes a competitive advantage over non‐bicarbonate users when the availability of carbon dioxide is limited due to the slow diffusion of CO 2 in dense plant stands or in alkaline waters of pH exceeding 8.…”
mentioning
confidence: 99%